Formulation, Optimization and Characterization of Bupropion Hydrochloride Loaded Nanostructured Lipid Carriers for Intra-Nasal Administration: An Approach to Management of Smoking Cessation - Rekharani, Aravind S.; Nidamanuri, Bala S. S.; Rajendra, Praharsh Kumar Mandadhi; Venkatachalam, Senthil; Selvaraj, Jubie; Natarajan, Jawahar (Current Nanomedicine, 2022)
Background: Tobacco smoking is a major factor leading to cardiovascular diseases. About 48% of cardiovascular diseases occur due to cigarette smoking. Bupropion hydrochloride is a non-nicotine treatment for smoking cessation. The existing marketed formulation of bupropion has limitations, like low bioavailability and extensive first-pass metabolism. In order to boost the bioavailability and increase the brain biodistribution of the drug, a colloidal drug delivery system, like nanostructured lipid carriers, is employed. Methods: NLC formulation was prepared using the microemulsion technique and an optimized formula was developed using a three-level factorial design. Results: The particle size of the optimized formulation was 162 nm, the polydispersity index was 12.2%, and the zeta potential was -29.0mV. Entrapment efficiency was found to be 41.2%. SEM images show that these NLCs are spherical. In vitro drug release study was conducted, and at the end of 72 hours, 50% of the drug was released, indicating the sustained release of the drug. Histopathological studies were conducted using goat nasal mucosa, and results indicated the NLC formulation as non-toxic for intranasal administration. Conclusion: Thus, through the intra-nasal route, an increased concentration of drug can be delivered to the brain via the olfactory pathway, thereby improving the therapeutic effect and exhibiting better patient compliance in smoking cessation.
Keywords: Nanostructured lipid carriers